B-type natriuretic peptide and N-terminal Pro-B-type natriuretic peptide in severe aortic stenosis: a comprehensive literature review - Cavalcante, Pâmela Nogueira; Kanhouche, Gabriel; Rosa, Vitor Emer Egypto; Campos, Carlos M.; Lopes, Mariana Pezzute; Lopes, Maria Antonieta Albanez A. de M.; Sampaio, Roney Orismar; Brito Júnior, Fábio Sândoli de; Tarasoutchi, Flavio; Abizaid, Alexandre Antonio Cunha (Frontiers in Cardiovascular Medicine, 2023)
B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT-pro BNP) are cardiac biomarkers that are released in response to increased ventricular and atrial wall stress. Aortic stenosis (AS) leads to hemodynamic changes and left ventricular hypertrophy and may be associated to natriuretic peptides levels. Several studies have shown that increased natriuretic peptide levels are correlated with AS severity and can predict the need for intervention. It can be useful in risk stratification, monitoring followup and predicting cardiovascular outcomes of patients with severe AS. This paper aims to summarize the evidence of the role of BNP and NT-pro BNP in AS, before and after intervention.